A cavity-shaped cis-chelating P, N ligand for highly selective nickel-catalysed ethylene dimerisation. Issue 30 (21st July 2022) - Li, Yang; Pelzer, Katrin; Sechet, Damien; Creste, Geordie; Matt, Dominique; Braunstein, Pierre; Armspach, Dominique
Abstract : The presence of a cyclodextrin cavity in a chelating P, N ligand promotes the exclusive formation of 1 : 1 ligand/metal complexes. A Ni(ii ) complex of the ligand is a very selective catalyst for ethylene dimerisation as a result of metal confinement. Abstract : The presence of a permethylated α-cyclodextrin (α-CD) cavity in a chelating P, N ligand promotes exclusive formation of 1 : 1 ligand/metal complexes. In MX2 complexes, one of the two halido ligands is forced to reside inside the CD hollow while the second one is pointing outside. Unlike its cavity-free analogue, a Ni(ii ) complex of the CD ligand is a highly selective precatalyst for ethylene dimerisation (96% C4 selectivity with up to 95% of 1-butene within the C4 fraction).